2023
DOI: 10.1590/1517-7076-rmat-2022-0260
|View full text |Cite
|
Sign up to set email alerts
|

Influence of strength behavior in brick masonry prism and wallette under compression

Abstract: For decades, prisms and wallette have been used to explore masonry's strength and deformation capabilities under uniaxial compression; moreover, the link between these two main test methods needs to be better established. Using standard masonry design expressions and data, the prism or wallette test can determine compression qualities. The researchers compared the standards and came to judgments on their conservatism or lack thereof, independent of how the rules for those design standards were formed. As a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The flexural strength by crack patterns variation is shown in Figure 4 and the test results. The M4 mix (10% AF + 100% OPC + 10% GD + 90% M Sand + 1% SP mix proportion is shown to be less similar, whereas the M5 mix (10% AF + 100% OPC+ 15% GD + 85% M Sand + 1% SP) is found to have the highest flexural strength [28,29]. The peak flexural strength is archived at M5 mix of 6.16 MPa and the least at M12 mix 5.76 MPa.…”
Section: Flexural Strength Testmentioning
confidence: 88%
“…The flexural strength by crack patterns variation is shown in Figure 4 and the test results. The M4 mix (10% AF + 100% OPC + 10% GD + 90% M Sand + 1% SP mix proportion is shown to be less similar, whereas the M5 mix (10% AF + 100% OPC+ 15% GD + 85% M Sand + 1% SP) is found to have the highest flexural strength [28,29]. The peak flexural strength is archived at M5 mix of 6.16 MPa and the least at M12 mix 5.76 MPa.…”
Section: Flexural Strength Testmentioning
confidence: 88%
“…The projected values from the ANFIS model built were very accurate. Furthermore, a comparison of the performance indices revealed that the ANFIS model performed somewhat better than the ANN model [48].…”
Section: Final Conclusionmentioning
confidence: 97%
“…Attempts to compare and implement the flexural behavior of concrete with developed analytical model [24]. Natural fibre like sisal and nano tubes as nano composites additionally brick aggregates also have introduced to study the performance of concrete [25][26][27][28]. Addition of pine apple fibre with granite powder enhances the performance of workability and stability [29].…”
Section: Introductionmentioning
confidence: 99%